Michelin Uptis - Are airless tires the future of the automotive industry? - Nikolov, Nikola Oka; Siegfried, Patrick; Ніколов, Нікола Ока; Зігфрід, Патрік (Харківський національний автомобільно-дорожній університет, 2023)
Problem. The paper addresses the question of whether the conversion of the entire automotive industry to airless tires, specifically focusing on the Michelin Uptis concept, is economically realistic and technically feasible for high-performance vehicles. Goal. The goal of the paper is to investigate and analyze the technical feasibility and economic impacts of airless tires, specifically the Michelin Uptis, through expert interviews, literature review, and research methodology. Methodology. The research methodology involves various research methods, including expert interviews, literature research, journal articles, press releases, and expert opinions. The paper relies on current and relevant sources to provide a comprehensive understanding of the topic. Expert interviews with industry professionals, such as Philipp Kranich from Mercedes Benz Consulting and Jochen Konrad, a tire developer at Pirelli, provide additional insights. Results. The technical feasibility of airless tires, specifically the Michelin Uptis, is examined, highlighting advantages such as puncture protection and environmental friendliness. However, concerns are raised regarding the structure's resilience, potential damage to spokes, weight and energy efficiency, and suitability for high-performance vehicles. The economic impacts of airless tires are also discussed, including the potential reduction in tire orders, changes in aftermarket services, logistical adaptations, and the pricing challenges associated with the Uptis concept. Originality and Practical Value. This paper offers an analysis of the technical and economic aspects of airless tires, specifically focusing on the Michelin Uptis concept. It provides expert insights, reviews relevant literature, and addresses the original research question. The findings contribute to the understanding of the feasibility and potential implications of airless tires in the automotive industry, aiding decision makers in assessing the practical value and viability of adopting this tire technology.
Michelin Uptis - Майбутнє автомобільної промисловості за безповітряними шинами?
Keywords: airless tires; Michelin Uptis; technical feasibility; economic impacts; automotive industry; безповітряні шини; технічна можливість; економічні наслідки; автомобільна промисловість; 629; 10.30977/AT.2219-8342.2023.52.0.11